2020
DOI: 10.3390/cells9020275
|View full text |Cite
|
Sign up to set email alerts
|

Type 3 Inositol 1,4,5-Trisphosphate Receptor is a Crucial Regulator of Calcium Dynamics Mediated by Endoplasmic Reticulum in HEK Cells

Abstract: Being the largest the Ca2+ store in mammalian cells, endoplasmic reticulum (ER)-mediated Ca2+ signalling often involves both Ca2+ release via inositol 1, 4, 5-trisphosphate receptors (IP3R) and store operated Ca2+ entries (SOCE) through Ca2+ release activated Ca2+ (CRAC) channels on plasma membrane (PM). IP3Rs are functionally coupled with CRAC channels and other Ca2+ handling proteins. However, it still remains less well defined as to whether IP3Rs could regulate ER-mediated Ca2+ signals independent of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 52 publications
(86 reference statements)
3
23
0
Order By: Relevance
“…Some of these observations are in agreement with previous studies. A lower rate of proliferation and migration in IP 3 R TKO HEK293 cells has been reported recently ( 31 ). A reduced baseline and FCCP-stimulated oxygen consumption was observed in Seahorse assays ( 85 ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Some of these observations are in agreement with previous studies. A lower rate of proliferation and migration in IP 3 R TKO HEK293 cells has been reported recently ( 31 ). A reduced baseline and FCCP-stimulated oxygen consumption was observed in Seahorse assays ( 85 ).…”
Section: Discussionmentioning
confidence: 65%
“…They concluded that, unlike normal cells, the stimulation of autophagy in cancer cells is not sufficient to compensate for the increased energy demand of uncontrolled growth, with cell death resulting from a “bioenergetic crisis” during mitosis. The advent of new methods of gene disruption has enabled all three IP 3 R isoforms to be deleted in human embryonic kidney 293 (HEK293) ( 30 , 31 ) and HeLa ( 32 ) human cancer cell lines. While these KO cells have primarily been used as an expression system to study the functional properties of IP 3 R mutants, they also offer the opportunity to investigate the metabolic and bioenergetic consequences of the chronic effects of a total loss of Ca 2+ signaling.…”
mentioning
confidence: 99%
“… 32 ITPR3 is a Ca 2+ release channel that resides in the membranes of the ER, which is extremely important for intracellular Ca 2+ homeostasis. 54 The present study revealed that the interaction of CEMIP and ITPR3 led to ER Ca 2+ leakage and increased cytosolic Ca 2+ levels in ECM‐detached PCa cells, subsequently activating CaMKII. Furthermore, functional studies revealed that CaMKII facilitates NRF2 phosphorylation at S40 and nuclear localization, leading to elevated SLC7A11 transcription in PCa cells.…”
Section: Discussionmentioning
confidence: 49%
“…Inositol‐1,4,5‐triphosphate (IP3) and its receptor IP3R located at the surface of the ER are responsible for regulating intracellular Ca 2+ release. [ 18 ] In principle, Mag‐Fluo‐AM, a type of fluorescent dye with low Ca 2+ affinity, is specifically captured by ER to detect the changes of Ca 2+ concentration and evaluate the transfer activity of IP3R. First, the IP3R activity was detected by an IP3R functional fluorescence detection kit (Shanghai Yuduo Biotech Ltd, China).…”
Section: Methodsmentioning
confidence: 99%